2007
DOI: 10.1159/000101775
|View full text |Cite
|
Sign up to set email alerts
|

Risk Prediction of Gastric Cancer by Analysis of Aberrant DNA Methylation in Non-Neoplastic Gastric Epithelium

Abstract: Background: Aberrant DNA methylation is one of the major events in carcinogenesis. Promoter DNA methylation is also present in various non-neoplastic tissues including gastric epithelium as age-related phenomenon, suggesting that it occurs early in the process of tumorigenesis. Aim: We aimed to clarify the relationship of aberrant DNA methylation in non-neoplastic gastric epithelia with the risk of gastric cancer, Helicobactor pylori infection, and the degree of H. pylori-induced gastritis. Methods: 89 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 43 publications
4
58
2
Order By: Relevance
“…The multivariate analysis showed that atrophic type or intestinal metaplasia was the strong independent risk for DNA methylation after H. pylori eradication. Although DNA hypermethylation might be a risk of gastric cancer regardless of H. pylori infection status [6,[19][20][21], in our study, the most important factor of DNA hypermethylation was magnifying NBI and histologic features. This indicates that the methylation change is closely linked to the magnifying NBI and histologic features within the focal points.…”
Section: Discussioncontrasting
confidence: 50%
“…The multivariate analysis showed that atrophic type or intestinal metaplasia was the strong independent risk for DNA methylation after H. pylori eradication. Although DNA hypermethylation might be a risk of gastric cancer regardless of H. pylori infection status [6,[19][20][21], in our study, the most important factor of DNA hypermethylation was magnifying NBI and histologic features. This indicates that the methylation change is closely linked to the magnifying NBI and histologic features within the focal points.…”
Section: Discussioncontrasting
confidence: 50%
“…One of the most important factors causing CIHM in the stomach is H. pylori infection (7,11,12), which induces chronic inflammation, causing oxidative stress to the gastric epithelium (16,17). Indeed, the methylation of certain genes in non-neoplastic gastric mucosa correlate with H. pylori related histological or serological severity of gastritis (12) and gastric cancer occurrence (13)(14)(15). Thus, this epigenetic change is thought to be an early step in gastric carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…To detect CIHM, we chose four candidate promoter CpG islands, which were thought to be most susceptible for methylation in the stomach (7,(11)(12)(13)(14)(15): p14, p16, DAP-kinase and CDH1. For the examination of DNA methylation, genomic DNA was treated with sodium bisulfite using BislFast DNA modification kit for methylated DNA detection (Toyobo, Co., Ltd., Osaka, Japan).…”
Section: Bisulfite Modification and Methylation-specifc Pcr (Msp)mentioning
confidence: 99%
See 2 more Smart Citations